Respostas
respondido por:
1
a)
f (x) = 3x - 7
0 = 3x - 7
7 = 3x
3x = 7
x = 7/3
b)
g (x)= 6x
0 = 6x
6x = 0
x = 0/6
x = 0
c)
n (x) =3x - (7x -1)
0 = 3x - 7x + 1
0 = - 4x + 1
4x = 1
x = 1/4
f (x) = 3x - 7
0 = 3x - 7
7 = 3x
3x = 7
x = 7/3
b)
g (x)= 6x
0 = 6x
6x = 0
x = 0/6
x = 0
c)
n (x) =3x - (7x -1)
0 = 3x - 7x + 1
0 = - 4x + 1
4x = 1
x = 1/4
respondido por:
0
Para encontrar o zero de uma função basta igualar ela a 0:
a)3x-7 = 0 ->
x = 7/3
b)6x = 0 ->
x = 0
c)3x-7x+1 = 0 ->
-4x = -1 ->
x = 1/4
a)3x-7 = 0 ->
x = 7/3
b)6x = 0 ->
x = 0
c)3x-7x+1 = 0 ->
-4x = -1 ->
x = 1/4
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás